2020
DOI: 10.1186/s41610-020-00154-x
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary antibiotic oxytetracycline’s effect on the soil microbial community

Abstract: Background: Antibiotics are widely used to treat animals from infections. After fertilizing, antibacterials can remain in the soil while adversely affecting the soil microorganisms. The concentration of oxytetracycline (OTC) in the soil and its effect on the soil microbial community was assessed. To assess the impact of OTC on the soil microbial community, it was added to the soil at concentrations of 50, 150, and 300 mg kg-1 and incubated for 35 days. Results: The concentration of OTC added to the soil decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…The persistence (in the case of OTC), or semi-persistence (in the case of CTC) of toxicity over time may be attributed to the slow degradation suffered by these antibiotics in soils [30][31][32], especially at high antibiotic concentrations [30,33]. In addition, Danilova et al [34] showed that the effects of OTC on the microbial community remain longer than the presence of antibiotics in soils. However, bacterial growth recovered over time in the presence of CTC, which may be attributed to ageing processes [35] or a bacterial community tolerance to antibiotics [36][37][38], but, further analysis is needed to clarify these possible mechanisms.…”
Section: Time-course Evolution Of Toxicity Due To Otc and Ctcmentioning
confidence: 99%
“…The persistence (in the case of OTC), or semi-persistence (in the case of CTC) of toxicity over time may be attributed to the slow degradation suffered by these antibiotics in soils [30][31][32], especially at high antibiotic concentrations [30,33]. In addition, Danilova et al [34] showed that the effects of OTC on the microbial community remain longer than the presence of antibiotics in soils. However, bacterial growth recovered over time in the presence of CTC, which may be attributed to ageing processes [35] or a bacterial community tolerance to antibiotics [36][37][38], but, further analysis is needed to clarify these possible mechanisms.…”
Section: Time-course Evolution Of Toxicity Due To Otc and Ctcmentioning
confidence: 99%
“…Algunos aspectos de la composición química del medio de cultivo, como la concentración de nitrógeno, generan un medio de control fisiológico y de regulación del metabolismo de los microorganismos (Thomas et al, 1996). Por otro lado, la oxitetraciclina (OTC), componente básico del agar OGYE, es un antibiótico ampliamente utilizado en la cría de animales, que trae como consecuencia la contaminación de agua, sedimentos, suelo, generando efectos negativos sobre la comunidad microbiana del suelo (Danilova et al, 2020). Migliore et al (2012) demostró por medio de análisis de espectrometría de masas que Pleurotus ostreatus (Jacq.)…”
Section: Discussionunclassified
“…Therefore, environmental contamination by antimicrobials and their residues interferes with the ecological functions of natural microbial populations [5,41]. Antimicrobial molecules can remain in soil and water for long periods, significantly modifying the dynamics of microbial populations, affecting their ability to metabolize carbon, limiting their enzymatic activity, and altering the relative abundance of microorganisms [36,42].…”
Section: Soil Contaminationmentioning
confidence: 99%
“…One study demonstrated that when the pollutant charge was not replaced, the concentration of antimicrobials in the soil decreased from 150 to 7.6 mg/kg after 30 days. However, despite this decrease, persistent antimicrobials still negatively influence soil microbial communities [41]. Furthermore, other studies have revealed that azithromycin and ciprofloxacin, for instance, degrade very slowly in the environment and can remain in the soil for 408 to 990 and 1155 to 3466 days, respectively [47].…”
Section: Soil Contaminationmentioning
confidence: 99%